2016
DOI: 10.1016/j.enbuild.2016.04.048
|View full text |Cite
|
Sign up to set email alerts
|

New method for the design of radiant floor cooling systems with solar radiation

Abstract: Impacts of solar shortwave radiation are not taken into account in the standardized design methods in the current radiant system design guidelines. Therefore, the current methods are not applicable for cases where incident solar is significant. The goals of this study are to: 1) use dynamic simulation tools to investigate the impacts of solar radiation on floor cooling capacity, and 2) develop a new simplified method to calculate radiant floor cooling capacity when direct solar radiation is present. We used En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 14 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…As the F-ratio was estimated with the steady-state calculation using a lighting simulation, Feng et al proposed a new equation to calculate the dynamic effect of direct solar radiation on the capacity of the radiant floor cooling. By using dynamic simulation, it was shown that the solar radiation absorption can increase the cooling capacity up to 130e140 W/m 2 [80]. Similarly, Arcuri et al [91] suggested the direct water load (DWL) to evaluate the real cooling capacity of a radiant ceiling panel, because the DWL is immediately removed by the radiant surface and it does not contribute to the cooling load of the indoor environment.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…As the F-ratio was estimated with the steady-state calculation using a lighting simulation, Feng et al proposed a new equation to calculate the dynamic effect of direct solar radiation on the capacity of the radiant floor cooling. By using dynamic simulation, it was shown that the solar radiation absorption can increase the cooling capacity up to 130e140 W/m 2 [80]. Similarly, Arcuri et al [91] suggested the direct water load (DWL) to evaluate the real cooling capacity of a radiant ceiling panel, because the DWL is immediately removed by the radiant surface and it does not contribute to the cooling load of the indoor environment.…”
Section: )mentioning
confidence: 99%
“…The other approach for the estimation represents the thermal capacity with a lumped thermal resistance and a mean temperature difference between the water and the room, as formulated in Eqs. (5)e(6) [80]. This approach exploits product data from the manufacturer in order to relate the thermal capacity to the system configuration and the water temperature.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of radiant floor cooling capacity in Xi'an Xianyang International Airport (Zhao et al, 2014) showed cooling capacities from 25 to 40 W/m 2 in areas with no direct solar exposure and 110 to 140 W/m 2 in locations directly exposed to the solar radiation. Feng et al, 2016 used EnergyPlus to simulate a total of 864 cases in which the window-to-wall ratio, building orientation, shading options and floor absorptivity varied, and concluded that radiant floor cooling capacity can vary between 20 and 44 W/m 2 without solar, and can go up to 150 W/m 2 with direct solar. Feng et al, 2016 also compared simulated capacities with the capacities calculated with ISO calculation method (ISO 2012) and concluded that the capacity is 1.2 to 2.7 times higher for the cases when floor is exposed to direct solar.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…We need to distinguish this term from the hydronic cooling capacity that refers to the amount of heat that is exchanged between the slab and hydronic tubing. A wide ranges of cooling capacities under solar radiation have been reported based on engineering judgment (100 -150 W/m 2 in Olesen, 1997;numerical calculations (up to 150 W/m 2 (Feng et al, 2016)), and field studies (110-140 W/m 2 (Zhao et al, 2014)). All the studies point out that cooling capacity of chilled radiant floors exposed to direct solar radiation require special consideration.…”
Section: Accepted Manuscriptmentioning
confidence: 99%